2020
DOI: 10.1186/s40359-020-00405-5
|View full text |Cite
|
Sign up to set email alerts
|

Construct and factorial validity of Neurobehavioral Disorder associated with Prenatal Alcohol Exposure (ND-PAE)

Abstract: Background ND-PAE, as a condition needing further study, requires validation. Few studies have assessed the validity of ND-PAE with none using a prospective sample. Methods Fifty-eight children underwent multidisciplinary FASD assessments and were evaluated for ND-PAE using a prospective, clinical approach. Construct and factorial validity of ND-PAE were assessed, and associations between domains and symptoms described. Post hoc analysis assessed external validity of factors. Results ND-PAE demonstrated weak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 39 publications
1
8
1
Order By: Relevance
“…Previous studies have assessed the validity of the diagnosis and have found that the AF domain may be too restrictive ( Kable & Coles, 2018 ). Specifically, requiring two out of four criteria for the AF domain (AF 2/4) may not be necessary, and requiring that one of the two first criteria for adaptive functioning (communication and social communication) is not supported by the literature and therefore may lead to low sensitivity, or fewer true positives ( Sanders et al, 2020 ). Sanders et al (2020) also evaluated construct and factorial validity of the ND-PAE diagnosis and found through principal component analysis (PCA) that symptoms only loaded on one factor, which included neurocognitive and adaptive functioning criteria.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies have assessed the validity of the diagnosis and have found that the AF domain may be too restrictive ( Kable & Coles, 2018 ). Specifically, requiring two out of four criteria for the AF domain (AF 2/4) may not be necessary, and requiring that one of the two first criteria for adaptive functioning (communication and social communication) is not supported by the literature and therefore may lead to low sensitivity, or fewer true positives ( Sanders et al, 2020 ). Sanders et al (2020) also evaluated construct and factorial validity of the ND-PAE diagnosis and found through principal component analysis (PCA) that symptoms only loaded on one factor, which included neurocognitive and adaptive functioning criteria.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, requiring two out of four criteria for the AF domain (AF 2/4) may not be necessary, and requiring that one of the two first criteria for adaptive functioning (communication and social communication) is not supported by the literature and therefore may lead to low sensitivity, or fewer true positives ( Sanders et al, 2020 ). Sanders et al (2020) also evaluated construct and factorial validity of the ND-PAE diagnosis and found through principal component analysis (PCA) that symptoms only loaded on one factor, which included neurocognitive and adaptive functioning criteria. Their assessment of convergent and divergent validity showed that convergence, or the correlation among symptoms, was low among SR symptoms, specifically the correlation between mood regulation and attention symptoms ( Sanders et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations